The female face of God in Auschwitz : a Jewish feminist theology of the Holocaust - Raphael, Melissa (Religion and gender., 2003)
The first full-length feminist dialogue with Holocaust theory, theology and social history. Considers women's reactions to the holy in the camps at Auschwitz.